Engineering Mouse Chromosomes with Cre-loxP: Range, Efficiency, and Somatic Applications - Binhai Zheng; Marijke Sage; Elizabeth A. Sheppeard; Vesna Jurecic; Allan Bradley (2000)
Chromosomal rearrangements are important resources for genetic studies. Recently, a Cre-loxP-based method to introduce defined chromosomal rearrangements (deletions, duplications, and inversions) into the mouse genome (chromosome engineering) has been established. To explore the limits of this technology systematically, we have evaluated this strategy on mouse chromosome 11. Although the efficiency of Cre-loxP-mediated recombination decreases with increasing genetic distance when the two endpoints are on the same chromosome, the efficiency is not limiting even when the genetic distance is maximized. Rearrangements encompassing up to three quarters of chromosome 11 have been constructed in mouse embryonic stem (ES) cells. While larger deletions may lead to ES cell lethality, smaller deletions can be produced very efficiently both in ES cells and in vivo in a tissue- or cell-type-specific manner. We conclude that any chromosomal rearrangement can be made in ES cells with the Cre-loxP strategy provided that it does not affect cell viability. In vivo chromosome engineering can be potentially used to achieve somatic losses of heterozygosity in creating mouse models of human cancers.